Early Detection For Better Results In The Treatment Of Asymptomatic Cases Of Valvular Heart Disease - Hutahaean, Gembira Ira; G Manik, Maria Ulfa (Indonesian Health Journal, 2024)
Valvular heart disease (VHD) often progresses asymptomatically, leading to delayed diagnosis and treatment, which worsens patient outcomes. Early detection of VHD in asymptomatic cases is crucial to improve treatment effectiveness and long-term prognosis. This study aims to investigate the impact of early detection on treatment outcomes in asymptomatic VHD patients. A cross-sectional study was conducted involving 200 patients diagnosed with VHD, categorized into two groups: those diagnosed early through screening and those diagnosed later after the onset of symptoms. Data were collected through medical records, echocardiograms, and patient interviews. Statistical analysis revealed that early detection significantly improved patient outcomes, with lower rates of complications, better valve repair success, and reduced mortality compared to those diagnosed later. Discussion centers on the importance of routine screenings in at-risk populations and the need for better diagnostic protocols to catch asymptomatic cases early. The conclusion highlights that early detection of asymptomatic VHD leads to better treatment outcomes, underlining the necessity of proactive screening measures to manage VHD effectively.